Kritik Muhammad Shahrur terhadap Asbab al-Nuzul dalam Penafsiran al-Qur’an - M. Thohar Al-Abza (Qur'an and Hadith Academic Society, 2012)
This article proves that Asbab al-Nuzul is an important element in interpreting the Qur’an and is a part of Ulum al-Qur’an. The result of this article has proven the weakness of Shahrur’s opinion (1938-...) expressing that present-time interpretation does not need the Asbab al-Nuzul, because, according to him, that tradition was only a form of history in interpretation, which is applicable only for the time of revelation, and not applicable in the present time. This article strengthens Abu Zaid’s opinion (1943-…) which considers Asbab al-Nuzul as historical information and as important element in Qur’anic interpretation at the same time. This article also supports Fazlurrahman’s view (d. 1988) which makes Asbab al-Nuzul – either in macro or in micro – as historical information that must be known and used in interpretation